Implementation of TTA pre-pack accreditation and training programme on paediatric wards. Issue 6 (9th May 2013) - Lo, A; Christiansen, N
Abstract : Aim: To implement a To Take Away (TTA) pre-pack accreditation programme and recording system for paediatric nurses to facilitate the safe dispensing of TTA pre-packs from wards. Method: To facilitate the prompt discharge of paediatric patients TTA pre-packs are dispensed by nurses from the wards for medicines prescribed on electronic TTAs. As paediatric dosing is complex and nurses do not have the same training as pharmacy staff to screen and dispense prescriptions, a validation programme was designed to train and accredit nursing staff. This consists of flow charts and monographs to screen, dispense and check prescribed medicines as well as recording patient details and the dispensed items. To restrict the scope of medicines supplied a limited list of TTA pre-packed medicines are stocked on wards. TTA pre-packs are chosen depending on the speciality of the ward and the focus is on high volume drugs. The programme consists of two parts: Part A contains the training and assessment material (flow charts for screening, dispensing and checking procedures) to be used whilst training and after accreditation. The screening procedure encompasses a drug monograph with information for the nurse to ascertain whether the drug is safe for the patient or not. Each drug has an individualised monograph that should be used with each dispensing and checking episode. Using competency grids in Part B and the checking test the training nurse must have their competency assessed and agreed to be competent by the assessor and signed off before checking alone. The training nurse is supervised dispensing and/or checking a number of separate TTA prescriptions having them double checked by an assessor (pharmacist or accredited nurse) until they feel confident to do the checking test. Nurses who undergo the accreditation programme must be senior band 5 or above. The checker must have been in post for at least 3 years. They must dispense and/or check at least 3 times before being signed off as competent. Reaccreditation is required by all every 2 years. Results: Three paediatric wards have now undertaken the training and use the validation programme with a further two wards half way through training. The short stay surgical and acute short stay medical unit ward finds the system very useful as it significantly reduces the waiting time for medicines prescribed to take home. There is increased confidence by nurses in dispensing these medicines as well as they have an accreditation system and drug monographs to use. The audit trail for any dispensed item is also available for analysing information. The use of pre-packs has also reduced pharmacy workload by way of fewer bleeps for validation and volume of work going through dispensary for commonly prescribed drugs. This has freed up time for more complicated prescriptions and makes better use of specialist pharmacist time. Conclusions: Implementation of this programme allows for the safe dispensing and checking of prescribed medicines on TTAs. This facilitates prompt discharges of patients thus reducing bed occupancy.